2017
DOI: 10.1007/s40520-016-0703-6
|View full text |Cite
|
Sign up to set email alerts
|

Objective measurement of gait parameters in healthy and cognitively impaired elderly using the dual-task paradigm

Abstract: ObjectivesThe present study explores the differences in gait parameters in elderly subjects with or without cognitive impairment measured by means of ambulatory actigraphy while performing a single and a dual task.MethodsSixty-nine participants of which 23 individuals were diagnosed with Alzheimer’s disease (AD), 24 individuals with mild cognitive impairment (MCI), and 22 healthy controls performed a single and dual walking task while wearing a wrist-worn accelerometer. Objective measures of gait features such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 38 publications
0
16
0
1
Order By: Relevance
“…Gait analysis is emerging as an effective tool to detect an incipient neurodegenerative disease or to monitor its progression [ 3 , 4 ]. It has been shown that gait disturbances are an early indicator for mild cognitive impairment (MCI) and can predict progression from MCI to Alzheimer’s disease [ 5 ]. Furthermore, gait performance is also a predictor of fall status [ 6 , 7 ], morbidity and mortality [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gait analysis is emerging as an effective tool to detect an incipient neurodegenerative disease or to monitor its progression [ 3 , 4 ]. It has been shown that gait disturbances are an early indicator for mild cognitive impairment (MCI) and can predict progression from MCI to Alzheimer’s disease [ 5 ]. Furthermore, gait performance is also a predictor of fall status [ 6 , 7 ], morbidity and mortality [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, the step variance remain constant also under the MCDT condition. Conclusively, the authors suggested that changes in gait induced by MCDT could be too subtle to be identified by a wrist-worn actigraph [König et al (2017)].…”
Section: The Use Of Wearable Sensors In Mcdt Assessment For MCI Subjectsmentioning
confidence: 99%
“…11,15 Tiene un valor predictivo, bien documentado, para hospitalizaciones, institucionalización en hogares de ancianos, mortalidad, mala calidad de vida, deterioro funcional físico y cognitivo y riesgo de caídas, lo que la convierte en una medida de detección útil para identificar a las personas mayores en riesgo de tales eventos. 8,11,[15][16][17][18] En Costa Rica, el envejecimiento de la población se ha acelerado, se estimaba envejecimiento acelerado, pasando del 7,6 % de personas adultas mayores en el año 2000, al 8,8 % para 2007, y una estimación del 11,5 % para 2025. 19 No obstante, en lo que a marcha respecta, no hay estudios clínicos en nuestra población y los equipos existentes en el mercado no incluyen bases de datos en población mayor de 60 años, por lo que no se cuenta con parámetros de normalidad.…”
Section: Fecha Recibido: 18 De Enero 2019unclassified